2020
DOI: 10.1177/1591019920954095
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular treatment of cerebral dural arteriovenous fistulas with SQUID 12

Abstract: Background Endovascular therapy with liquid embolic agents (LEAs) is the gold standard for the treatment of cerebral dural arteriovenous fistulas (cDAVFs). The aim of the study is to retrospectively evaluate effectiveness, safety, and midterm follow-up results of endovascular treatment of cDAVFs using SQUID 12. Methods Between June 2017 and January 2020 the authors retrospectively reviewed clinical, demographic and embolization data of 19 consecutive patients with cDAVF who underwent embolization using SQUID 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 20 publications
1
20
0
Order By: Relevance
“…Two experimental studies, focusing on the extra-low viscosity version of PHIL (explained in more detail below), used Squid 12 as a comparator and showed that the embolization using the extra-low viscous LEAs Squid 12 and PHIL LV can be more effective than the standard viscous versions in terms of a higher embolization extent and fewer reflux events [65,66]. These findings were also described in a few clinical studies; however, further studies are needed to further analyze potential advantages and disadvantages of Squid 12 and Squid 12LD [65][66][67].…”
Section: Embolic Propertiesmentioning
confidence: 87%
“…Two experimental studies, focusing on the extra-low viscosity version of PHIL (explained in more detail below), used Squid 12 as a comparator and showed that the embolization using the extra-low viscous LEAs Squid 12 and PHIL LV can be more effective than the standard viscous versions in terms of a higher embolization extent and fewer reflux events [65,66]. These findings were also described in a few clinical studies; however, further studies are needed to further analyze potential advantages and disadvantages of Squid 12 and Squid 12LD [65][66][67].…”
Section: Embolic Propertiesmentioning
confidence: 87%
“…The two best known non-adhesive EVOH liquid embolic agents are Onyx and Squid, both available in different formulations characterised by variable viscosity. They are similar but Squid, marketed more recently, is also available in the less viscous formulation which spreads more distally and may be useful in selected cases, as for example to treat arteriovenous malformations [8,14]. Another advantage of Squid over Onyx is the reduced percentage (less 30%) and smaller size of tantalum particles conditioning fewer metallic artefacts on CT images [15,16].…”
Section: Discussionmentioning
confidence: 99%
“…Advantages of detachable coils, nowadays less expensive than in the past, are their marked radiopacity and their capability to be removed and replaced when necessary, whilst their major limit is the achievement of a complete and permanent occlusion [6]. Non-adhesive, ethylene-vinyl alcohol (EVOH) liquid embolic agents mixed with micronised tantalum powder and dissolved in dimethyl sulfoxide (DMSO), as Onyx and Squid, were mainly used in the cerebral district [7,8]. However, they have recently also used in abdominal diseases, alone as in endoleak embolisation [9,10] or associated with coils for treating splenic [11] or renal aneurysms [12].…”
Section: Introductionmentioning
confidence: 99%
“…Squid presents some advantages over Onyx: a less tantalum percentage associated with smaller particles reduces artifacts at CT follow-up. Moreover, Squid is also available in the less viscous formulation 12, which allows a more distal spread in small vessels, particularly useful in arteriovenous malformations [ 73 , 74 ]. Phil is the most recent of the EVOH embolic agents and still lacks a solid grounding in literature, but seems to present some advantages over Onyx (and Squid): fewer CT-artifacts due to the use of iodine contrast instead of tantalum, quicker preparation without shaking, “toothpaste-like” instead of “lava-like” consistency which allows a quicker injection, yellow color instead of black powdered material which does not stain the skin in case of embolization of superficial lesions [ 67 , 75 ].…”
Section: Embolization: Techniques and Materialsmentioning
confidence: 99%